Indigenous Knowledge of Medicinal Plants in Tribal Community of Antri and Mewara Forest Range of Dungarpur District, Rajasthan - Patidar, Savitri (Asian Journal of Pharmaceutical Research and Development, 2023)
Indigenous knowledge is a valuable knowledge that has been facilitated local ethno- groups of people for survival in all over the world. This knowledge is unique tactic knowledge that originates from the interaction between members of the community and the environment in which they live. It passes through elder generations to younger generations orally or verbally. Knowledge about ethno-medicinal plants and practices make it a survival strategy of livelihood in tribal community of Dungarpur district. However, Dungarpur district is enriched with Deciduous forest covered thus abundant of medicinal plants are identified by these group of people for healthcare purposes. This study is an attempt to identify the ethno-medicinal plants and documentations it with special case studies of the persons who authentically treat and cure community. The field survey was carried out during January 2022 to March 2022 and in July 2022 for identification of plants and know about their story. Outcomes from the field survey revealed that abundant of ethno-medicinal species are found in this area due to its Geographical and Climatic conditions. Since, lack of awareness, lesser interest of Government and local politicians and integument of modernity over younger generation this knowledge has been extinct gradually from the society. There should me need to conserve and protect their traditional legacy of survival with nature.